Trust, variability in relationship evaluations, and relationship processes.[article]. - Koo, Minjung
Little is known about why some people experience greater temporal fluctuations of relationship perceptions over short periods of time, or how these fluctuations within individuals are associated with relational processes that can destabilize relationships. Two studies were conducted to address these questions. In study 1, long-term dating partners completed a 14-day diary study that assessed each partner's daily partner and relationship perceptions. Following the diary phase, each couple was videotaped trying to resolve the most important unresolved problem from the diary period. as predicted, (a)individuals who trusted their partners less reported greater variability in perceptions of relationship quality across the diary period. (b)they also perceived daily relationship-based conflict as a relatively more negative experience; and (c)greater variability in relationship perceptions predicted greater self-reported distress, more negative behavior, and less positive behavior during a post diary conflict resolution task (rated by observers). The diary results were conceptually replicated in Study 2a, in which older cohabiting couples completed a 21-day diary. These participants also took part in a reaction-time decision-making study (Study 2b), which revealed that individuals tend to compartmentalize positive and negative features of their partners if they (individuals) experienced greater variability in relationship quality during the 21-day diary period and were involved in higher quality relationships. These findings advance researchers' understanding of trust in intimate relationships and provide some insight into how temporal fluctuations in relationship quality may undermine relationships. -- (from the author)